2022
DOI: 10.1097/naq.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Executive Experiences With COVID-19

Abstract: We conducted semistructured telephone interviews with 2 hospital-based nurse leaders who supervised nurses during the initial phases of the COVID-19 pandemic in northeastern region of the United States. These interviews are a subset of a larger study with 11 nurse executives who supervised nurses during both natural and human-made disasters in different regions of the United States. Qualitative data were analyzed using a grounded theory approach, followed by a content analysis of emerging themes. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Similarly, participants voiced feelings of guilt and angst between personal and family safety and a sense of professional duty (Sterling et al, 2020). Langan et al (2022) also referred to the pandemic experience like a “ continuous roller coaster ride ” for nurse executives demonstrating that all levels of providers may have shared similar emotional responses despite proximity to direct patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, participants voiced feelings of guilt and angst between personal and family safety and a sense of professional duty (Sterling et al, 2020). Langan et al (2022) also referred to the pandemic experience like a “ continuous roller coaster ride ” for nurse executives demonstrating that all levels of providers may have shared similar emotional responses despite proximity to direct patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Home care leaders need to be visible and transparent to reduce emotional uncertainties that negatively affect patients and staff. When leaders listen to staff and provide opportunities to give input into solving practice problems, they allow providers to feel they are part of the solution (Jones et al, 2020; Langan et al, 2022). Kelley et al (2022) also found that clear communication in an organized and strategic fashion from leadership to the frontline was important to providers.…”
Section: Discussionmentioning
confidence: 99%